Finite element simulation of laser shock forming - Soh, Kian Ann. (2013)
This project studies the feasibility of applying finite element analysis (FEA) to simulate high strain rate forming of thin copper foil during the Laser Shock Forming (LSF) process, thereby predicting their ultimate deformation. ABAQUS, a commercial finite element software, was used in this study. This report traces the development process of the finite element modelling, which includes the theoretical research, the development of the simulation model, and the verification of the simulation result by means of comparing with results from literature.